2006
DOI: 10.1007/11732242_6
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Risk Type Classification from Protein Sequences Using Support Vector Machines

Abstract: Abstract. Infection by the human papillomavirus (HPV) is associated with the development of cervical cancer. HPV can be classified to highand low-risk type according to its malignant potential, and detection of the risk type is important to understand the mechanisms and diagnose potential patients. In this paper, we classify the HPV protein sequences by support vector machines. A string kernel is introduced to discriminate HPV protein sequences. The kernel emphasizes amino acids pairs with a distance. In the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…They also further developed the better algorithm based on geometric moments of protein distance matrix images using a Fuzzy K nearest neighbor classifier [ 10 ]. In addition, classification of HPV risk types was also proposed through algorithms based on decision tree [ 11 ], text mining [ 12 ], genetic mining of DNA sequence structures [ 13 ], support vector machines [ 14 ], gap-spectrum kernels [ 15 ], and ensemble support vector machines with protein secondary structures [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also further developed the better algorithm based on geometric moments of protein distance matrix images using a Fuzzy K nearest neighbor classifier [ 10 ]. In addition, classification of HPV risk types was also proposed through algorithms based on decision tree [ 11 ], text mining [ 12 ], genetic mining of DNA sequence structures [ 13 ], support vector machines [ 14 ], gap-spectrum kernels [ 15 ], and ensemble support vector machines with protein secondary structures [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Support Vector Machines (SVM). SVM is a discriminant classifier, which is defined by the classification hyperplane [27]. In other words, the labeled training samples are used to train the model, and then the test sample classification is realized by outputting the best hyperplane [67].…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…Through systematic analysis, Park et al suggested using decision tree to construct the typing model of human papillomavirus [ 25 ]. Kim and Zhang calculated the distance distribution of amino acid pairs and further predicted the risk type of HPV through E6 protein [ 26 , 27 ]. Kim et al extracted the differential features of protein secondary structure and designed a set of support vector machine (GSVM) to classify HPV types [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human papillomaviruses are icosahedral, nonenveloped particles that contain a small, double-stranded circular DNA of approximately 8000 nucleotide base pairs [ 8 ] and belong to the Papillomavirus family (papilloma, polyoma, and simian vacuolating viruses) [ 9 ]. The diameter of circular DNA is approximately 55 nm [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Park et al proposed a classification of the risk type of human papillomavirus by decision tree [ 26 ]. Kim and Zhang introduced the string kernel and Gap-spectrum kernel to compute the distances of amino acids pairs and further used them to classify HPV risk types based on E6 protein sequences [ 7 , 9 ]. Kim et al proposed an Ensemble support vector machine to classify HPV risk types based on the differential subsequences of protein secondary structures [ 13 ].…”
Section: Introductionmentioning
confidence: 99%